TRANSFORMING AI AND MACHINE LEARNING: THE ROLE OF CUSTOM ASIC CHIPS IN AI ACCELERATION - Ramalinga Reddy Kotapati, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The rapid evolution of artificial intelligence and machine learning has intensified the demand for efficient computing solutions, leading to the emergence of Application-Specific Integrated Circuits (ASICs) as a transformative technology. These custom-designed chips offer unprecedented performance improvements and energy efficiency gains compared to traditional general-purpose processors. ASICs achieve this through specialized architectures featuring massive parallel processing arrays, optimized memory hierarchies, and sophisticated power management systems. The integration of automated design optimization and high-level synthesis tools has further enhanced their capabilities, enabling adaptable solutions for diverse AI workloads. Despite challenges in design complexity and the balance between specialization and flexibility, ASICs have demonstrated significant advantages in operational costs and environmental impact reduction. The technology continues to advance through innovations in memory systems, packaging technologies, and reconfigurable architectures, while the market expands across cloud computing, edge applications, and enterprise deployments. The emergence of domain-specific accelerators and the growing adoption of custom solutions indicate a fundamental shift in AI computing infrastructure.